1989
DOI: 10.1098/rspa.1989.0031
|View full text |Cite
|
Sign up to set email alerts
|

On the stability limit of charged droplets

Abstract: Single, highly charged droplets of dioctylphthalate and sulphuric acid of radius between 1 and 10 μm are suspended in vacuum in a quadrupol trap. As the droplets evaporate their radius is monitored continuously by light scattering and their charge is determined periodically by weight balancing. The droplets break when the electric stress exceeds that of surface tension. The largest fragment remains trapped allowing a determination of the change in volume and charge. The fraction of volume and charge lost is fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
1

Year Published

2000
2000
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(26 citation statements)
references
References 17 publications
2
23
1
Order By: Relevance
“…However, since we have observed that the width of the cloud of possible charge versus diameter states encountered spans approximately one unit in the z axis, such hypothetical Coulomb explosions would have to always eject a single charge. Yet, Coulomb explosions from high conductivity drops tend to eject up to 50% of the drop charge (eight charges rather than one for z ϭ 16; [33]). Furthermore, since we know the diameter and the charge for all our residues, we can compute the ratio of their actual charge to Rayleigh's limiting charge.…”
Section: Can Our Observations Be Explained Without the Ion Evaporatiomentioning
confidence: 99%
“…However, since we have observed that the width of the cloud of possible charge versus diameter states encountered spans approximately one unit in the z axis, such hypothetical Coulomb explosions would have to always eject a single charge. Yet, Coulomb explosions from high conductivity drops tend to eject up to 50% of the drop charge (eight charges rather than one for z ϭ 16; [33]). Furthermore, since we know the diameter and the charge for all our residues, we can compute the ratio of their actual charge to Rayleigh's limiting charge.…”
Section: Can Our Observations Be Explained Without the Ion Evaporatiomentioning
confidence: 99%
“…It is notable that the measured critical charge for a particular liquid was similar, even for different sized droplets, and that it was different for each liquid which may suggest the critical charge depends in some way on the material w x properties. Measurements by Richardson et al 6 for charged drop stability were made using an electrodynamic w x levitator. As in the previous instance by Taflin et al 5 , light scattering techniques were used to measure droplet size, which gave good accuracy.…”
Section: Manuscript Recei®ed On 30 December 2003 In Final Formmentioning
confidence: 99%
“…Richardson et al (1989) reported an extreme case of the "fine fission" mode for a droplet of sulfuric acid. The charge loss was about 50 % but no mass loss was observed.…”
Section: Rayleigh Instability Of Charged Dropletsmentioning
confidence: 99%
“…Richardson et al (1989) used a cylindrical and two hemispherical cap electrodes to measure the Rayleigh instability of charged droplets. Davis and Bridges (1994) examined the cause of charged droplet fission prior to reaching the Rayleigh instability limit by using two different sets of double ring electrodes.…”
Section: Introductionmentioning
confidence: 99%